Influence of rivet length on joint formation on self-piercing riveting process considering further process parameters - Kappe, Fabian; Bielak, Christian Roman; Sartisson, Vadim; Bobbert, Mathias; Meschut, Gerson (ESAFORM 2021)
Driven by the CO2-emission law by the European government and the increasing costs for raw materials as well as energy, the automotive industry is increasingly using multi-material constructions. This leads to a continuous increase in the use of mechanical joining techniques and especially the self-piercing riveting is of particular importance. The reason for this is the wide range of joining possibilities as well as the high load-bearing capacities of the joints. To be able to react to changing boundary conditions, like material thickness or strength variation of the sheets, research work is crucial with regard to the increase of versatility. In this paper, a numerical study of the influences on the selfpiercing riveting process is presented. For this purpose, the influence of different process parameters such as rivet length and die depth on various quality-relevant characteristics were investigated. With the help of the design of experiment, significant influences were determined and interactions between the individual parameters are shown.

Influence of various procedures for the determination of flow curves on the predictive accuracy of numerical simulations for mechanical joining processes - Böhnke, Max; Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Materials Testing)
The predictive quality of numerical simulations for mechanical joining processes depends on the implemented material model, especially regarding the plasticity of the joining parts. Therefore, experimental material characterization processes are conducted to determine the material properties of sheet metal and generate flow curves. In this regard, there are a number of procedures which are accompanied by varying experimental efforts. This paper presents various methods of determining flow curves for HCT590X as well as EN AW-6014, including varying specimen geometries and diverse hardening laws for extrapolation procedures. The flow curves thus generated are compared considering the variety of plastic strains occurring in mechanical joining processes. The material data generated are implemented in simulation models for the joining technologies, clinching and self-piercing riveting. The influence of the varied methods on the predictive accuracy of the simulation model is analysed. The evaluation of the differing flow curves is achieved by comparing the geometric formation of the joints and the required joining forces of the processes with experimentally investigated joints.

New Approach for Versatile Self Piercing Riveting: Joining System and Auxiliary Part - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
The increasing use of multi-material constructions lead to a continuous increase in the use of mechanical joining techniques due to the wide range of joining possibilities as well as the high load-bearing capacities of the joints. Nevertheless, the currently rigid tool systems are not able to react to changing boundary conditions, like changing the material-geometry-combination. Therefore research work is crucial with regard to versatile joining systems. In this paper, a new approach for a versatile self-piercing riveting process considering the joining system as well as the auxiliary joining part is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Investigation of the influence of varying tumbling strategies on a tumbling self-piercing riveting process - Wituschek, Simon; Kappe, Fabian; Lechner, Michael (Production Engineering)

Load Path Transmission in Joining Elements - Steinfelder, Christian; Martin, Sven; Brosius, Alexander; Tröster, Thomas (Key Engineering Materials)
The mechanical properties of joined structures are determined considerably by the chosen joining technology. With the aim of providing a method that enables a faster and more profound decision-making in the spatial distribution of joining points during product development, a new method for the load path analysis of joining points is presented. For an exemplary car body, the load type in the joining elements, i.e. pure tensile, shear and combined tensile-shear loads, is determined using finite element analysis (FEA). Based on the evaluated loads, the resulting load paths in selected joining points are analyzed using a 2D FE-model of a clinching point. State of the art methods for load path analysis are dependent on the selected coordinate system or the existing stress state. Thus, a general statement about the load transmission path is not possible at this time. Here, a novel method for the analysis of load paths is used, which is independent of the alignment of the analyzed geometry. The basic assumption of the new load path analysis method was confirmed by using a simple specimen with a square hole in different orientations. The results presented here show a possibility to display the load transmission path invariantly. In further steps, the method will be extended for 3D analysis and the investigation of more complex assemblies. The primary goal of this methodical approach is an even load distribution over the joining elements and the component. This will provide a basis for future design approaches aimed at reducing the number of joining elements in joined structures.

Joint point loadings in car bodies – the influence of manufacturing tolerances and scatter in material properties - Martin, Sven; Tröster, Thomas (ESAFORM 2021)

Joining with versatile joining elements formed by friction spinning - Wischer, Christian; Wiens, Eugen; Homberg, Werner (Journal of Advanced Joining Processes)

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, Daniel; Sadeghian, Behdad; Kupfer, Robert; Troschitz, Juliane; Gude, Maik; Brosius, Alexander (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, Benjamin; Köhler, Daniel; Vorderbrüggen, Julian; Troschitz, Juliane; Kupfer, Robert; Meschut, Gerson; Gude, Maik (Production Engineering)
Abstract Recent developments in automotive and aircraft industry towards a multi-material design pose challenges for modern joining technologies due to different mechanical properties and material compositions of various materials such as composites and metals. Therefore, mechanical joining technologies like clinching are in the focus of current research activities. For multi-material joints of metals and thermoplastic composites thermally assisted clinching processes with advanced tool concepts are well developed. The material-specific properties of fibre-reinforced thermoplastics have a significant influence on the joining process and the resulting material structure in the joining zone. For this reason, it is important to investigate these influences in detail and to understand the phenomena occurring during the joining process. Additionally, this provides the basis for a validation of a numerical simulation of such joining processes. In this paper, the material structure in a joint resulting from a thermally assisted clinching process is investigated. The joining partners are an aluminium sheet and a thermoplastic composite (organo sheet). Using computed tomography enables a three-dimensional investigation that allows a detailed analysis of the phenomena in different joining stages and in the material structure of the finished joint. Consequently, this study provides a more detailed understanding of the material behavior of thermoplastic composites during thermally assisted clinching.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

In Situ Computed Tomography—Analysis of a Single-Lap Shear Test with Clinch Points - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (Materials)
As lightweight design gains more and more attention, time and cost-efficient joining methods such as clinching are becoming more popular. A clinch point’s quality is usually determined by ex situ destructive analyses such as microsectioning. However, these methods do not yield the detection of phenomena occurring during loading such as elastic deformations and cracks that close after unloading. Alternatively, in situ computed tomography (in situ CT) can be used to investigate the loading process of clinch points. In this paper, a method for in situ CT analysis of a single-lap shear test with clinched metal sheets is presented at the example of a clinched joint with two 2 mm thick aluminum sheets. Furthermore, the potential of this method to validate numerical simulations is shown. Since the sheets’ surfaces are locally in contact with each other, the interface between both aluminum sheets and therefore the exact contour of the joining partners is difficult to identify in CT analyses. To compensate for this, the application of copper varnish between the sheets is investigated. The best in situ CT results are achieved with both sheets treated. It showed that with this treatment, in situ CT is suitable to properly observe the three-dimensional deformation behavior and to identify the failure modes.
Keywords: General Materials Science

Clinching in In-situ CT – Experimental Study on Suitable Tool Materials - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (ESAFORM 2021)
In lightweight design, clinching is a cost-efficient solution as the joint is created through localized cold-forming of the joining parts. A clinch point’s quality is usually assessed using ex-situ destructive testing methods. These, however, are unable to detect phenomena immediately during the joining process. For instance, elastic deformations reverse and cracks close after unloading. In-situ methods such as the force-displacement evaluation are used to control a clinching process, though deviations in the clinch point geometry cannot be derived with this method. To overcome these limitations, the clinching process can be investigated using in-situ computed tomography (in-situ CT). However, a clinching tool made of steel would cause strong artefacts and a high attenuation in the CT measurement, reducing the significance of this method. Additionally, when joining parts of the same material, the sheet-sheet interface is hardly detectable. This work aims at identifying, firstly, tool materials that allow artefact-reduced CT measurements during clinching, and, secondly, radiopaque materials that can be applied between the joining parts to enhance the detectability of the sheet-sheet interface. Therefore, both CT-suitable tool materials and radiopaque materials are selected and experimentally investigated. In the clinching process, two aluminium sheets with radiopaque material in between are clinched in a single-step (rotationally symmetric joint without cut section). It is shown that e.g. silicon nitride is suited as tool material and a tin layer is suitable to enhance the detectability of the sheet-sheet interface.

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)

Identification of joints for a load-adapted shape in a body in white using steady state vehicle simulations - Martin, Sven; Schütte, Jan; Bäumler, C.; Sextro, Walter; Tröster, Thomas (Forces in Mechanics)

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Influence of Kinematic Hardening on Clinch Joining of Dual-Phase Steel HCT590X Sheet Metal - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (The Minerals, Metals & Materials Series)
Nowadays, clinching is a widely used joining technique, where sheets are joined by pure deformation to create an interlock without the need for auxiliary parts. This leads to advantages such as reduced joining time and manufacturing costs. On the other hand, the joint strength solely relies on directed material deformation, which renders an accurate material modelling essential to reliably predict the joint forming. The formation of the joint locally involves large plastic strains and possibly complex non-proportional loading paths, as typical of many metal forming applications. Consequently, a finite plasticity formulation is utilised incorporating a Chaboche–Rousselier kinematic hardening law to capture the Bauschinger effect. Material parameters are identified from tension–compression tests on miniature spec- imens for the dual-phase steel HCT590X. The resulting material model is implemented in LS-Dyna to study the locally diverse loading paths and give a quantitative statement on the importance of kinematic hardening for clinching. It turns out that the Bauschinger effect mainly affects the springback of the sheets and has a smaller effect on the joint forming itself.
Keywords: Clinching; Material modelling; Kinematic hardening; Parameter identification; Bauschinger effect

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, L.; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, M. (Production Engineering)
In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Clinching in In Situ CT—A Novel Validation Method for Mechanical Joining Processes - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (The Minerals, Metals & Materials Series)
Force–displacement measurements and micrograph analyses are commonly used methods to validate numerical models of clinching processes. However, these methods often lead to resetting of elastic deformations and crack- closing after unloading. In contrast, the in situ computed tomography (CT) can provide three-dimensional images of the clinch point under loading conditions. In this paper, the potential of the in situ investigation of a clinching process as validation method is analyzed. For the in situ testing, a tailored test set-up featuring a beryllium cylinder for load-bearing and clinching tools made from ultra-high-strength titanium and Si3N4 are used. In the experiments, the clinching of two aluminum sheets is interrupted at specific process steps in order to perform the CT scans. It is shown that in situ CT visualizes the inner geometry of the joint at high precision and that this method is suitable to validate numerical models.
Keywords: Clinching; Non-destructive testing; Computed tomography; In situ CT

Investigation of the influence of formed, non-rotationally symmetrical pin geometries and their effect on the joint quality of steel and aluminium sheets by direct pin pressing - Römisch, David; Kraus, Martin; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight-construction technologies a current trend. For this reason, multi-material-systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by cold formed pin structures has shown to have high potential for joining multi-material-systems. These pins can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pins are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form-fit joint. Usually, cylindrical pins are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pins as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X+Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut has an crucial influence on the joint strength, the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined to analyse the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension tests. Here the flow resistance of the geometry used as well as the pin height and thus the strain hardening of the pin base during the extrusion of the pins play a decisive role for the shear strength.
Keywords: Mechanical Engineering; General Materials Science